Interaction of mono- and divalent metallic cations and of indomethacin on the membrane potential of vascular endothelial cells in vitro. - Northover, B J (1975)
1 Endothelial cells depolarized progressively when heated for 5 h at 45 degrees C in the presence of calcium (1 mM), cupric (0.08 mM) or ferrous (0.04mM) ions. In the absence of these ions, heating caused only slight depolarization. Higher concentrations of these ions caused depolarization even at normal body temperature (37 degrees C). 2 Cuprous and potassium ions, although producing depolarization at 37 degrees C, failed to augment the depolarization due to heating to 45 degrees C. 3 Hydrogen peroxide caused depolarization which was potentiated by the presence of calcium, cupric or ferrous ions, but not by the presence of cuprous or potassium ions. 4 Indomethacin (0.25 mM) reduced the depolarization caused by calcium, cupric or ferrous ions at 37 degrees C and also reduced the potentiation of heat-induced and hydrogen peroxide-induced depolarization which these divalent metallic cations produced. However, indomethacin failed to modify the depolarization caused by cuprous or potassium ions.